Geographical and Logistic Aspects of Urbotourism Sustainable Development Under the Conditions of Overtourism Extension - Ihor Smyrnov (Вісник Київського національного університету культури і мистецтв. Серія: Туризм, 2019)
A new phenomenon in tourism in the early 21st century is overtourism, which reflects the acute nature of the problem of managing growing tourist flows, especially in urban areas. The increasing number of urban tourists increases the consumption of natural and tourist resources of cities, exerts socio-cultural influence and exerts pressure on urban infrastructure. Therefore, for urban tourism, it is now an important task to effectively manage the flow of tourists in cities to ensure the sustainability of integrated urban development. Strategies, measures and proposals for sustainable urban tourism development include mandatory consideration of logistical and socio geographical (regional) features of urban tourist destinations.